A monoclonal antibody against the receptor for advanced glycation end products attenuates inflammatory and neuropathic pain in the mouse. (22nd September 2015) - Brederson, J.‐D.; Strakhova, M.; Mills, C.; Barlow, E.; Meyer, A.; Nimmrich, V.; Leddy, M.; Simler, G.; Schmidt, M.; Jarvis, M.; Lacy, S.
Abstract: Background: The receptor for advanced glycation end products (RAGE) is a multi‐ligand receptor in the immunoglobulin superfamily. RAGE is localized throughout ascending sensory pathways (skin, peripheral nerve, dorsal root ganglion, spinal cord), and in cell types interacting with sensory neurons (endothelial cells, smooth muscle cells, monocytes and macrophages). Neuronal RAGE expression increases in pathological pain states in humans and rodents, and soluble RAGE attenuates thermal hypoalgesia in diabetic mice. The objective of the present study was to investigate whether pharmacological modulation of RAGE could attenuate mechanical allodynia in rodent pain models. Methods: We developed an anti‐RAGE monoclonal antibody (11E6) that binds to the C2 immunoglobulin domain of human RAGE, binds to mouse RAGE, and presumably to the same domain in mouse RAGE. The antinociceptive activity of 11E6 was investigated in mouse models of inflammatory (complete Freund's adjuvant) and neuropathic (chronic constriction injury of the sciatic nerve) pain. Mice were dosed intraperitoneally with 11E6 or IgG (negative control). Results: Increased mechanical thresholds were observed following a single dose of 11E6 in both inflammatory and neuropathic pain models. Similar treatment with IgG did not alter nociceptive sensitivity. Repeated dosing with 11E6 significantly attenuated established mechanical hypersensitivity in a neuropathic pain model in a dose‐related fashion. Conclusions: These data demonstrate that specific modulation of RAGE effectively attenuates nociceptive sensitivity associated with chronic inflammatory and neuropathic pain states.